Field Information Web Platform for Agricultural Applications - Leote, Gonçalo José Esteves (2019)
Crops are subject to numerous diseases and pests that may cause significant economic damage. It is essential to forecast the potential occurrence of the major problems in these crops. The goal of this dissertation is the development of a web platform for registration and issuance of warnings of disease’s risk. The generation of these warnings is performed using mathematical models to predict possible occurrence of plant diseases and/or the collection of information in the field by farmers and/or technical experts by means of mobile devices. This information should be geo-referenced and can be obtained with mobile devices which could be documented with photos, videos, text, data from satellite, weather data, web information or even with information from sensors on the ground. This thesis describes and shows a fully working platform that is able to collect data and compute alerts from the several sources of information available, in a scalable way.